2013
DOI: 10.1101/gr.157743.113
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale hypomethylated blocks associated with Epstein-Barr virus–induced B-cell immortalization

Abstract: Altered DNA methylation occurs ubiquitously in human cancer from the earliest measurable stages. A cogent approach to understanding the mechanism and timing of altered DNA methylation is to analyze it in the context of carcinogenesis by a defined agent. Epstein-Barr virus (EBV) is a human oncogenic herpesvirus associated with lymphoma and nasopharyngeal carcinoma, but also used commonly in the laboratory to immortalize human B-cells in culture. Here we have performed whole-genome bisulfite sequencing of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 45 publications
9
151
1
Order By: Relevance
“…EBV-induced immortalization of B-cells resembling post-transplant lymphoproliferative disease caused extensive changes in the B-cell methylome affecting 2.18 GB of the cellular genome and about onethird of all genes [60]. Strikingly, overlapping hypomethylated blocks of 1.7 GB were also observed in the epigenomes of unrelated EBV-negative carcinomas, including colon, lung, breast and thyroid carcinomas and Wilms' tumors [54].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…EBV-induced immortalization of B-cells resembling post-transplant lymphoproliferative disease caused extensive changes in the B-cell methylome affecting 2.18 GB of the cellular genome and about onethird of all genes [60]. Strikingly, overlapping hypomethylated blocks of 1.7 GB were also observed in the epigenomes of unrelated EBV-negative carcinomas, including colon, lung, breast and thyroid carcinomas and Wilms' tumors [54].…”
Section: Discussionmentioning
confidence: 92%
“…For the development of EBV-associated lymphomas and carcinomas, epigenetic dysregulation plays an outstanding role, with specific methylation profiles characterizing the different entities posttransplant lymphoproliferative disease, Burkitt lymphoma, Hodgkin lymphoma, nasopharyngeal carcinoma, and gastric carcinoma [60][61][62]. EBV-induced immortalization of B-cells resembling post-transplant lymphoproliferative disease caused extensive changes in the B-cell methylome affecting 2.18 GB of the cellular genome and about onethird of all genes [60].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, B cell immortalization by EBV resulted in large-scale hypomethylation that affected two-thirds of the B cell genome. Promoter hypomethylation of a number of proliferative genes was consistent with the conversion of resting B cells to proliferating blasts (26,27). EBV infection of germinal center B cells not only was shown to alter DNMT expression, resulting in changed DNA methylation patterns at particular regions, but also induced the histone 3 lysine 27 demethylase, KDM6B, potentially regulating genes differentially expressed in Hodgkin's lymphoma (28,29).…”
mentioning
confidence: 90%
“…We focused on CpG methylation because the distribution of CpG methylation is altered in various EBV-associated malignancies (9,(15)(16)(17)(18)(19)(20)(21). EBV immortalization of B cells has been shown to be associated with large-scale hypomethylation that affected twothirds of the B cell genome and led to promoter hypomethylation of a number of proliferative genes, consistent with the conversion of resting B cells to proliferating blasts (26,27). In contrast, EBVassociated gastric and nasopharyngeal carcinomas display hypermethylation at a number of tumor suppressor gene promoters (17)(18)(19)(20).…”
Section: Generation Of Ebv-negative Transiently Infected Clonesmentioning
confidence: 99%
“…Transformation of primary B cells leads to genomewide transcriptional changes including a decrease of apoptotic genes and an increase of proliferative genes (Allday 2013;Price and Luftig 2014;Price et al 2017). EBV-induced transformation of primary B cells also leads to DNA hypomethylation at about two-thirds of the genome (Hernando et al 2013;Hansen et al 2014). It has furthermore been found that EBV infection in primary B cells transactivates a human ERV locus, HERV-K18, leading to the expression of a superantigen important for T cell response (Sutkowski et al 1996).…”
Section: Introductionmentioning
confidence: 99%